Perjalanan Politik Hukum Pertanahan Dalam Memberikan Perlindungan Terhadap Kepemilikan Hak Atas Tanah Masyarakat Indonesia - Baiq Riska Anggi Safitri; Kris Wardiansyah; Nuyun Nurillah (Peneliti.net, 2023)
Land provides a means of livelihood as it embodies the spirit of dignity, prosperity, sanctity, and even power. As a result, everyone strives hard to obtain and maintain land, both individually and as a society. Recognizing the importance of land ownership to every individual, the state mandates the leaders of the Republic of Indonesia based on Article 33, paragraph (3) of the 1945 Constitution of the Republic of Indonesia to regulate the utilization of natural resources, especially land, in order to improve the prosperity of all Indonesian people. This mandate is regulated in Article 33, paragraph (3) of the 1945 Constitution of the Republic of Indonesia as the basis and guiding principle for the politics of land and other natural resources. These requirements are eventually translated into Law Number 5 of 1960 concerning Basic Agrarian Regulations, commonly known as the Basic Agrarian Law, with a consistent and progressive spirit (UUPA). The purpose of this research is to understand the political and legal journey of land in Indonesia and to determine the legal certainty of land politics in providing protection for land ownership rights of Indonesian society. This research is a normative study with a legislative and conceptual approach. The data collection technique in this research is carried out through literature review (library research).